Continuous ultraviolet to blue-green astrocomb - Cheng, Yuk Shan; Dadi, Kamalesh; Mitchell, Toby; Thompson, Samantha; Piskunov, Nikolai; Wright, Lewis D.; Gawith, Corin B. E.; McCracken, Richard A.; Reid, Derryck T. (Nature communications, 2024)
Cosmological and exoplanetary science using transformative telescopes like the ELT will demand precise calibration of astrophysical spectrographs in the blue-green, where stellar absorption lines are most abundant. Astrocombs—lasers providing a broadband sequence of regularly-spaced optical frequencies on a multi-GHz grid—promise an atomically-traceable calibration scale, but their realization in the blue-green is challenging for current infrared-laser-based technology. Here, we introduce a concept achieving a broad, continuous spectrum by combining second-harmonic generation and sum-frequency-mixing in an MgO:PPLN waveguide to generate 390–520 nm light from a 1 GHz Ti:sapphire frequency comb. Using a Fabry-Pérot filter, we extract a 30 GHz sub-comb spanning 392–472 nm, visualizing its thousands of modes on a high-resolution spectrograph. Experimental data and simulations demonstrate how the approach can bridge the spectral gap present in second-harmonic-only conversion. Requiring only ≈ 100 pJ pulses, our concept establishes a new route to broadband UV-visible generation at GHz repetition rates. Astrocombs serve as precision calibrators for astrophysical spectrographs by providing a regular sequence of optical lines on a multi-GHz grid. Here, the authors report the first broadband astrocomb in the UV to blue-green spectral region, where stellar absorption lines are most abundant.